Eco-logie in conflitto: il «Chipko» da protesta contadina a icona ambientalista. - Federica Riva (Glocalism: Journal of Culture, Politics and Innovation, 2014)
The article explores different cultural perceptions of food in relation to the environment. ‘Farmers’ and ‘ecologists’ are often actors of contrasting eco-logics: antithetic visions of the environment, as rural landscape or wilderness, define the right or ban of people to get access to the natural resources as commons in order to produce livelihood.